(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In order to improve digital literacy competence, digital content models learning based on social sciences in the user-generated content platform as a media literacy is made to educate people using research and development methods. The subject of this study involved respondents at junior high schools, students at higher levels, and citizens. This method was chosen as a step in developing educational products. In this research, the digital content model becomes a tested model through a small-scale phased test mechanism. The developed digital content model consists of six components, namely: social sciences education, writing, knowledge, digital media, search engine optimization (SEO), and digital copyright. The digital content generated is then released on the User Generated Content Platform. The implementation of this digital content model shows a significant change regarding digital literacy competencies, which effectively increases digital literacy competencies by 35.77% in the small-scale testing. The results of this study are digital content models for social studies education to support the creation of a digital literacy culture for students and the public in the era of global competence in line with the government’s efforts to promote digital literacy.